2017
DOI: 10.14295/cs.v8i1.1379
|View full text |Cite
|
Sign up to set email alerts
|

Seed germination and vigor of passion fruit hybrids

Abstract: Most commercial plantations of passion fruit is propagate plants by seed, but germination is irregular, which hinders the growth of seedlings and uniformity, and is connected with the plant genotype. The objective of this study was to evaluate the germination and early growth of passion fruit hybrid seedlings, obtained from different genetic combinations. The hybrids were obtained from the cross between progenies from the breeding program of the Universidade Federal de Viçosa with hybrids of the Empresa Brasil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In this way, we selected those that most contributed to the analysis, since the GroundEye equipment provides a high number of variables. Seventeen seed color, geometry, and texture variables that contributed with more than 5% to the importance of traits of each individual group were thus used; color variables below the Otsu threshold: CIELab a, CIELab dispersion, CIELab dispersion of L, and CIELab L, black dominance, hue variance; geometric variables: Feret diameter, number of Harris corners, medium area, larger area, smaller area, and elliptical variation; texture variables: Haralick contrast, Haralick dissimilarity, RunLength HGRE (high gray-level run emphasis), RunLength LRHGE (long-run, high gray-level emphasis) and RunLength SRHGE (short-run, high gray-level emphasis) (Xu et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, we selected those that most contributed to the analysis, since the GroundEye equipment provides a high number of variables. Seventeen seed color, geometry, and texture variables that contributed with more than 5% to the importance of traits of each individual group were thus used; color variables below the Otsu threshold: CIELab a, CIELab dispersion, CIELab dispersion of L, and CIELab L, black dominance, hue variance; geometric variables: Feret diameter, number of Harris corners, medium area, larger area, smaller area, and elliptical variation; texture variables: Haralick contrast, Haralick dissimilarity, RunLength HGRE (high gray-level run emphasis), RunLength LRHGE (long-run, high gray-level emphasis) and RunLength SRHGE (short-run, high gray-level emphasis) (Xu et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…edulis, in turn, has a high germination rate, as demonstrated in the study of Santos et al (2015), who obtained percentages higher than 90% in seven genotypes in open and self-pollination, which were carried out in the bud stage aiming to overcome self-incompatibility. In the case of hybrids from passionfruit progeny, the germination percentage ranged from 3% to 84% (Souto et al, 2017).…”
Section: Sj % Valuementioning
confidence: 99%
“…The greatest numerical value of the emergence speed index among all crosses and structures was obtained by the hybrid of crosses 02 (4.41). The rate obtained by the hybrid crosses 02 was higher than those found by Souto et al (2017b), that studied germination and emergence speed index and found a value of 4.00 for the best treatment (genotype/hybrid 02). The high emergence speed index and quick emergence of the seedlings in a shorter period play an important role in genotype vigor and uniformity in establishing plants and seedlings production.…”
Section: Resultsmentioning
confidence: 60%
“…Thus, one of the great challenges that breeders faced is to group into a genotype the greatest number of desirable traits and, in the case of SPF, to obtain fruits with high quality, resistance to the main diseases and seeds with high germinative potential. The percentage of germination and vigor of seedlings are factors that must be considered in the genetic breeding of SPF (SOUTO et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, passion fruit breeding programs have considered the genetic influence in expressing seed quality, such as germination, emergence and vigor of seedlings (Souto et al, 2017). Alexandre et al (2004) observed that germination and emergence speed in passion fruit are influenced by the seed genotype.…”
Section: Introductionmentioning
confidence: 99%